A full-range moisture sorption model for cellulose-based materials yielding consistent net isosteric heat of sorption. Issue 1 (3rd January 2023) - Tryding, Johan; Askfelt, Henrik; Alexandersson, Marcus; Ristinmaa, Matti
Abstract: A structured approach to derive the water activity function of cellulose-based materials which describe the sorption behavior from dry fiber up to the fiber saturation point is proposed. The coupling between the sorption isotherm and the net isosteric heat of sorption is incorporated in a consistent way, which allows for coupled heat-diffusion problems to be solved. Three different models are derived, generalizations of the classic Oswin and Henderson isotherm models and a new model denoted LW. Experimental data from the literature is used to evaluate and compare model performance to the GAB model, and it is shown that generalizations of the classic Oswin, Henderson isotherms and the new LW model perform well.